Muscle ring finger-1 is required to prevent age-related cardiac hypertrophy and interstitial remodelling. (25th November 2020) - Zaglia, T; Prando, V; Parry, T.L; Scalco, A; Pesce, P; Tang, W; Ma, H; Braghetta, P; Basso, C; Faggian, G; Bonaldo, P; Sandri, M; et al.
Abstract: Purpose: The Ubiquitin Proteasome System (UPS) is a selective degradation system mediating the removal of intracellular unfolded/misfolded proteins and is essential for cardiomyocyte (CM) health. Substrate specificity and ubiquitination rate are mediated by E3 ubiquitin-ligases, such as Atrogin1 and MuRF1, which are specifically expressed in muscle cells. Perturbation of protein quality control causes aggregation of misfolded proteins, leading to CM proteotoxicity. UPS dysfunction occurs in ageing, a risk factor for cardiac hypertrophy and HF. We recently demonstrated that Atrogin-1 is essential to maintain CM health, during ageing. Whether MuRF1 plays similar roles in heart adaptation to ageing is still unexplored, and different studies have yielded contrasting results. Methods: To assess the role of MuRF1 in heart homeostasis, we combined echocardiography, histology, IF, TUNEL assay and EM on heart sections from MuRF1 knock-out (KO) mice, and littermate controls, at 3, 10 and 24 mo. RTqPCR and WB assessed markers of UPS and extracellular matrix. Langendorff procedure was used to separate CMs from cardiac fibroblasts. Molecular and IF analyses were performed in heart samples from patients affected by aortic stenosis. Results: MuRF1 ablation leads to cardiac hypertrophy, progressing during ageing (LV CM areas: 3 mo., KO: 329.14±10.66 vs Ctrl: 296.25±5.43; 10 mo., KO: 399.73±7.64 vs Ctrl: 247.49±3.67; 24 mo., KO: 418.89±11.10 vs. Ctrl: 209.93±4.48, in μm 2 ). The hypertrophic remodeling was accompanied by diastolic dysfunction in the adulthood and, during ageing, also by systolic dysfunction (EF, 24 mo., KO: 29.55±8.82 vs Ctrl: 51.23±6.56, in %). Loss of MuRF1 causes increased interstitial collagen -I and -VI deposition, even before the onset of contractile dysfunction, followed by activation of Matrix MetalloProteinases (MMPs), suggesting that such alterations may be responsible for decreased cardiac performance. Interestingly, collagen established rings enveloping MuRF1 KO CMs and such fibrotic remodeling was not accompanied by increased CM apoptosis, nor myofibroblast activation. Such peculiar remodelling, called peri-endomysial fibrosis, was detected in hearts from patients with aortic stenosis, a condition in which MuRF1 levels decrease. Our data supports that MuRF1 has a role in CM-dependent regulation of the extracellular matrix (ECM) dynamics. Consistently, MuRF1 downregulation in normal cultured CMs demonstrated that such ubiquitin ligase impacts on signaling pathways involved in the control of the ECM homeostasis. In addition, fibroblasts treated with culture medium conditioned by MuRF1 KO CM display increased collagen and MMP expression. Conclusions: We identifieded a novel role of MuRF1 in the control of CM proteostasis, and unveiled that in addition to cardiac fibroblasts, CM may directly regulate ECM dynamics, indicating that the correct function of MuRF1 is essential for heart adaptation to aging. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): University of Padova